Lizards of Brazilian Amazonia (Reptilia: Squamata) - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1995)
Eighty-nine species of lizards, six of which polytypic (forming a total of 97 taxa), are presently known from Brazilian Amazonia. This number includes six species and one subspecies described as new to science in this paper: Stenocercus fimbriatus, Lepidoblepharis hoogmoedi, Leposoma osvaldoi, L. snethlageae, Tretioscincus oriximinensis, Tupinambis longilineus, and Anolis nitens tandai. Stenocercus dumerilii is resurrected from the synonymy of S. tricristatus. Bachia cophias is considered a junior synonym of B. flavescens. B. peruana is a new record from Brazil. Anolis nitens has priority over A. chrysolepis. The Amazonian Tupinambis is shown to be T. teguixin (of which T. nigropunctatus is a junior synonym). The name T. merianae should be used for T. teguixin sensu Boulenger (1885b). Mabuya ficta is a junior synonym of M. bistriata, while the name M. nigropunctata should be used for M. bistriata sensu Vanzolini & Williams (1980). Of all species extensive descriptions and ecological data, if available, are presented. A zoogeographical analysis based on the combined distribution maps of the various species shows a main division in Amazonia of a western and an eastern fauna. A southwestern group is also recognised and, although defined by a smaller number of species, a Guianan group. The lizard fauna from Rondônia shows multiple affinities. The distribution of lizards in enclaves of open formations in Amazonia does not support the idea of continuous areas of savannas throughout Amazonia in relatively recent times.
Lagartos da Amazônia brasileira (Reptilia: Squamata)
Keywords: Reptilia; Squamata; Amazonia; Taxonomia; Zoogeografia; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES